THE INFLUENCE OF THE MEDIA ON JURY TRIAL DECISIONS: A STUDY ON THE IMPACT OF PUBLIC OPINION ON CRIMINAL PROCEEDINGS (REMUNOM, 2026)
The present undergraduate thesis aims to analyse how media coverage influences the impartiality and decisions rendered by the Jury Court, especially in cases of major social impact. This qualitative and explanatory research employed a bibliographic review and the analysis of real cases, such as the Boate Kiss, Flordelis, and Henry Borel cases, to identify patterns of media interference in jury decisions. The findings indicate that sensationalist journalism tends to anticipate judgments and shape public opinion, thereby undermining the constitutional principles of the presumption of innocence, due process of law, and impartiality. It is concluded that, although freedom of the press is a fundamental right, ethical and legal boundaries must be established to prevent media influence from compromising the legitimacy of the Jury Court and the effectiveness of criminal justice. Furthermore, the study proposes measures to raise awareness and promote critical thinking among jurors, as well as greater social responsibility from the media, to harmonize freedom of expression with the right to a fair trial.